2018
DOI: 10.1002/term.2685
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable tubular collagen implants

Abstract: Collagen has been extensively used as a biomaterial, yet for tubular organ repair, synthetic polymers or metals (e.g., stents) are typically used. In this study, we report a novel type of tubular implant solely consisting of type I collagen, suitable to self‐expand in case of minimal invasive implantation. Potential benefits of this collagen scaffold over conventional materials include improved endothelialization, biodegradation over time, and possibilities to add bioactive components to the scaffold, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…When our crimped plug with shape memory comes into contact with PBS, it fully returns to the shape in which it was crosslinked, while the untreated plugs did not show any shape recovery. The mechanism of the shape memory has been proposed before by our laboratory in both self-closing and self-expandable tubular scaffolds [ [33] , [34] , [35] ]. The degree of expansion of the crosslinked solid plugs in solvents with different polarities showed comparable results with the expandable tubular scaffolds [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When our crimped plug with shape memory comes into contact with PBS, it fully returns to the shape in which it was crosslinked, while the untreated plugs did not show any shape recovery. The mechanism of the shape memory has been proposed before by our laboratory in both self-closing and self-expandable tubular scaffolds [ [33] , [34] , [35] ]. The degree of expansion of the crosslinked solid plugs in solvents with different polarities showed comparable results with the expandable tubular scaffolds [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we communicated how shape memory can be given to hollow tubular scaffolds made of exclusively type I collagen fibrils [ [33] , [34] , [35] ]. In this study, we constructed a solid, non-hollow collagen plug with shape memory to expand directly upon employment in order to seal fetal membranes after a fetoscopic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that such engineered substitutes successfully displayed elastic-like characteristics. This type of scaffold was described as the first self-expandable tubular implant consisting solely of type I collagen [34].…”
Section: Biological Scaffoldsmentioning
confidence: 99%
“…It has been proven that the use of fresh water fish scale-derived collagen is advantageous due to its enhanced biocompatibility and high level of direct cell adhesion [ 16 ]. Since fish collagen loses stability at body temperature [ 17 ], it has to be cross-linked in order to maintain its spongy consistency when used as a collagen dressing [ 16 , 18 ]; carbodiimide has been demonstrated to provide a highly biocompatible collagen cross-linking agent [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%